Studying of Different Activity Equations Effect for Estimate Binary Systems Pressure - Ahmadi, T.; Zareei, F.; Zare Valuekolayi, H.; Soleimani Lashkenari, M. (Asian Journal of Chemistry, 2011)
The calculation of VLE’s parameters in diverse system is important with assumed equality fugacity of two phases. In this study prediction binary system pressure by diverse activity equation was fitted by Matlab software and comparison of experimental and calculated pressure versus mole fraction was drawn (P-X). The vapour phase was assumed as an ideal gas. Finally error of calculated pressure was determined. Binary system studied are N-methyl pyrrolidone-1,3-butadiene. It can be concluded that optimization could be used for such systems.